INTERPROFESSIONAL ATTITUDES INFLUENCE THE READINESS OF HEALTH CARE PROFESSIONS STUDENTS FOR INTERPROFESSIONAL LEARNING - Catharina Dwiana Wijayanti; Kristina Lisum (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Background and Purpose: Collaboration among health care profession is required to create synergism in delivering health care at various clinical setting. This collaboration should be initiated at the academic setting through interprofessional learning. The Purpose of this research was to identify the influence of interprofessional attitudes to readiness of health care professions students for interprofessional learning.Method: Research method used quantitative with descriptive comparative design and cross sectional approaches. RIPLS and IPAS survey were completed by 180 medical and nursing students. Results: The majority of respondents were 20 years old, 134 were female and 53 respondents were in second year level. From Chi square statistic analysis, it was found that that there were no relationship between age, gender and level of academic with readiness for interprofessional learning (pvalue >.05). However, there was a significant relationship between interprofessional attitude of medical (p=.000; α=.05) and nursing students (p= .001 α=.05) with readiness for interprofessional learning. Conclusion and recommendation: It was suggested that interprofessional attitudes of health care professions students should be develop properly in the academic settings, thus it will bridge the gap between others health care professions.